Book Review Studio Properties: A Field Guide to Design Education - Buck, Lyndon; Underwood, Gary; Conrad, Franziska (Design and Technology Education: An International Journal, 2025)
There is something special about a studio as a place of practice and learning, and Studio Properties seeks to be a field guide to the design studio in education, presenting a single reference source for research and scholarship in this area. The authors explain that the Studio Properties project, and the Studio Matters project before it, were motivated by the absence of a comprehensive reference text of scholarship on studio pedagogy aimed at scholars and educators. Theoretical works and teaching guides exist but tend to focus on certain aspects of the studio and no single text brings these ideas together under the idea of Studio. It aims to allow educators and researchers to quickly find and directly apply content to their own disciplines and contexts.